Semi-compatible mappings and common fixed point theorems of an implicit relation via inverse $ C- $class functions - Zhou, Mi; Jain, Mukesh Kumar; Khan, Mohammad Saeed; Secelean, Nicolae Adrian (AIMS mathematics, 2021)
In this paper, we prove some common fixed point theorems by exploring a new kind of generalized semi-compatibility and an implicit relation via inverse $ C- $class functions. The results generalize, extend and improve the main results of [19 , 21 , 22 , 23 ] . Moreover, some examples are given to illustrate the validity of our results.